Unity out of Diversity : the Origins and Development of the University of Humberside. - David Foster, Dom (Continuum International Pub. Group, 2000)
This history of the University traces the formation of the College of Higher Education in 1976 from a number of diverse institutions, dating from 1861 onwards, its progress to the foundation of the University in the context of public policy and local authority frameworks. In this respect, the book is more than a history of an individual institution: it relates the development of higher education in Hull to local, regional and national patterns of provision.